Familial duodenal ulcer and Helicobacter pylori - Aizen, Bernardo; Mescia, Carlos; Bortagaray, Graciela; Scigliano, Horacio; Piana, Ana María; Bergalli, Luis (Cirugía del Uruguay, 1994)
A description is given of a familia/ group wherein ali members shared the same dwe/ling and were sufferers of gastritis and duodenal ulcers; members exhibited gastric colonization by Helicobacter pylori (H.P.) the antimicrobial treatment of which has so far attained the eradication of the germ and the cure of the ulcero-peptic disease. A discussion is carried out of the gene tic origin of the familia/ duodenal ulcer; a/so described are the characteristics of the germ (H.P.), its association with the gastroduodenal pathology, therapeutics and epidemiology. The condition traces the origin of the current familia/ ailment and deals with successfu/ therapy underlying the resolution of the pathology.